Who Needs Educational Portals? A Survey on Users and Usage - Petko, Dominik; Egger, Nives (Swiss Journal of Educational Research, 2015)
A survey of 2432 users and non-users of the Swiss Educational Server showed that the portals’ free information resources are not as well known and as widely used as expected. Instead, the communication tools offered by the portal’s learning management system are better known and used more often. In addition, differential analyses show that teachers at higher levels of the educational system as well as education policy-makers are likelier to use the educational portal than teachers at lower levels. Moreover, it was shown that individuals with higher media affinity used the services offered by the Swiss Educational Services significantly more frequently. The findings provide an incentive for reevaluating the services of educational portals. In the future, portals could put greater emphasis on their role as «trusted platform providers» rather than as «trusted information providers».